Welfare Cost of (Low) Inflation : A General Equilibrium Perspective - Zee, Howell (IMF Working Papers; Working Paper ;, 1998)
This paper provides general equilibrium estimates of the steady-state welfare gains of lowering inflation from a low level to close to price stability, using an overlapping-generations growth model. Money demand is modeled on the basis that real money balances are a factor of production. Assuming a standard Fisher equation modified by the presence of an income tax, it is found that inflation unambiguously reduces capital intensity, drives up the before-tax real rate of return to capital, and unambiguously imposes a life-time welfare cost. This welfare cost is, however, quantitatively very modest (under 0.2 percent of GDP annually) within reasonable ranges of all parameter values.